2017
DOI: 10.1038/s41598-017-17929-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrafascial and non-intrafascial radical prostatectomy for low risk localized prostate cancer

Abstract: In this meta-analysis study, we compared the oncological and functional outcomes of intrafascial radical prostatectomy (IFRP) with non-intrafascial radical prostatectomy (NIFRP) in the treatment of patients with low risk localized prostate cancer (PCa). Relevant articles were identified by searching PubMed, EMBASE, Cochrane Library, Ovid, and the ISI Web of Knowledge databases. A total of 2096 patients were included from 7 eligible studies. Results of the pooled data showed that the oncological outcomes includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For novice surgeons, intrafascial radical prostatectomy other than the non-intrafascial technique was suggested in young patients with a low risk of localized prostate cancer. 17 The duration of catheter placement was slightly long in the single-knot group because two cases in the single-knot group had a catheter for longer than 1 month and surgeons with limited experienced wanted to guarantee anastomosis. Postoperative prostate-specific antigen levels were detectable because of the high positive margin rate, but this was acceptable for novice surgeons who had not overcome the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…For novice surgeons, intrafascial radical prostatectomy other than the non-intrafascial technique was suggested in young patients with a low risk of localized prostate cancer. 17 The duration of catheter placement was slightly long in the single-knot group because two cases in the single-knot group had a catheter for longer than 1 month and surgeons with limited experienced wanted to guarantee anastomosis. Postoperative prostate-specific antigen levels were detectable because of the high positive margin rate, but this was acceptable for novice surgeons who had not overcome the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al in a meta-analysis including 2096 patients from 7 eligible studies, compared the oncological and functional outcomes of intrafascial with non-intrafascial RP (including interfascial, extrafascial and no nerve-sparing approaches) in patients with low-risk localized prostate cancer. Meta-analysis demonstrated that the oncological outcomes were similar between the two groups, while the intrafascial approach was associated with lower postoperative complication rates, higher continence rates at 3 months and higher potency rates at 6 and 12 months following surgery, as compared to the non-intrafascial approaches [ 21 ].…”
Section: The Fascial Planes For Nsmentioning
confidence: 99%